(untitled) (Global Journal of Computer Science and Technology, 2014)
Abstract- The rapid growth in the usage of the internet had led to many serious security issues in the network The intrusion detection system IDS is one of the sophisticated defensive systems used to detect the malicious activities happening in the network services across the world Hence more advanced IDS are been developed in past few years To improve the performance of the IDS the system has to be trained effectively to increase the efficiency and decrease the false alarm rate To train the system the attributes selection plays the major role This paper evaluates and compares the performance of the intrusion detection systems for different feature reduction techniques in high speed networks